A note on sightings of bowhead whales in the North Water Polynya, Northern Baffin Bay, May-June, 1998 - Holst, M.; Stirling, I. (J. Cetacean Res. Manage., 2023)
As part of a multidisciplinary research cruise by icebreaker in the North Water Polynya in northern Baffin Bay, we conducted shipboard surveys of marine mammal distribution and abundance throughout the area from April to July 1998. Fourteen sightings of at least ten individual bowhead whales (Balaena mysticetus) were made during May and June. Five additional large baleen whales, whose identities were not confirmed, were also seen. As well as being an important feeding ground, the polynya may also serve as an overwintering site for bowhead whales of the Davis Strait/Baffin Bay stock.